Analisis Faktor Yang Mempengaruhi Penerimaan Teknologi Pada Pengguna Aplikasi Shopee Menggunakan Technology Acceptance Model (TAM) - Helena Hervilia; Dayan Singasatia; M. Agus Sunandar (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
E-commerce is an online shopping platform that is getting public attention because it can be an alternative for convenience in meeting the consumptive needs of the community. One of them is Shopee, which is the most superior in Indonesia, being the most remembered and most widely used e-commerce brand by most people, it was recorded that Shopee visitors in 2021 were 33.27 million visitors. To find out what factors affect the acceptance of shopee application users using the Technology Acceptance Model (TAM) method with 4 (four) variables, namely Perceived usefulness, Perceived ease of use, Attitude toward using, Behavioral intention to use and 1 (One) Perceived variable. enjoyment as an external factor. While testing the hypothesis using Structural Equation Modeling (SEM). From the results of this study, there is a positive and significant influence between Perceived ease of use, Perceived enjoyment and Attitude toward using on behavioral intention to use. Meanwhile, for the perceived usefulness variable, perceived enjoyment of attitude toward using and behavioral intention to use, there is no positive and significant effect.